Precursor-Engineered Volatile Inks Enable Reliable Blade-Coating of Cesium–Formamidinium Perovskites Toward Fully Printed Solar Modules - Du, Tian; Rehm, Viktor; Qiu, Shudi; Pal, Subhajit; Jang, Dongju; Peng, Zijian; Zhang, Jiyun; Yuan, Haozhen; Briscoe, Joe; Heiß, Wolfgang; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Science, 2024)
Reliable fabrication of large-area perovskite films with antisolvent-free printing techniques requires high-volatility solvents, such as 2-methoxyethanol (2ME), to formulate precursor inks. However, the fabrication of high-quality cesium–formamidinium (Cs–FA) perovskites has been hampered using volatile solvents due to their poor coordination with the perovskite precursors. Here, this issue is resolved by re-formulating a 2ME-based Cs0.05FA0.95PbI3 ink using pre-synthesized single crystals as the precursor instead of the conventional mixture of raw powders. The key to obtaining high-quality Cs–FA films lies in the removal of colloidal particles from the ink and hence the suppression of colloid-induced heterogeneous nucleation, which kinetically facilitates the growth of as-formed crystals toward larger grains and improved film crystallinity. Employing the precursor-engineered volatile ink in the vacuum-free, fully printing processing of solar cells (with carbon electrode), a power conversion efficiency (PCE) of 19.3%, a T80 (80% of initial PCE) of 1000 h in ISOS-L-2I (85 °C/1 Sun) aging test and a substantially reduced bill of materials are obtained. The reliable coating methodology ultimately enables the fabrication of carbon-electrode mini solar modules with a stabilized PCE of 16.2% (average 15.6%) representing the record value among the fully printed counterparts and a key milestone toward meeting the objectives for a scalable photovoltaic technology.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cesium formamidinium perovskite; reliable blade coating; single crystals; solar module; volatile ink